Taxonomic studies on Ophiorrhiza in Vietnam I: Ophiorrhiza hiepii and O. hainanensis, a new species and new record from northern Vietnam - Liu, Wen-Jian; Gao, Qi; Nguyen, Khang Sinh; Nguyen, Dzu Van; Wu, Lei (Phytotaxa, 2020)
Ophiorrhiza hiepii and O. hainanensis are reported as a new species and a new record for Vietnam respectively. O. hiepii is morphologically similar to O. subrubescens but differs by its smaller habit, usually unbranched stems, fewer secondary veins, umbelliform and sub-congested cymes, shorter corolla tubes and shorter stigma lobes in short-styled flowers. The mature flowers of O. hainanensis, which were unknown before, were measured in the wild for supplemental description of its floral characters. Additionally, the relationship between O. hainanensis and O. nutans, two easily confused species is clarified.